Contextual influences on the visual sensitivity of moving and static patterns - Chambers, Alison L. (2016)
Spatial context can have a profound modulatory influence on visual sensitivity. Psychophysical evidence of contextual interactions is widespread reporting both facilitative and suppressive influences of objects placed near to target stimuli. A large part of the work in this thesis was motivated by the findings of Roach et al. (2011). They revealed the ability to detect a sinusoidal target abutting the leading edge of a drifting grating was highly dependent on the relative phase of the two stimuli, whereas performance at the trailing edge was not. To gain a more detailed understanding of the mechanisms underlying this phase-dependent modulation, we investigated its dependency on several different characteristics of the stimuli. These included its spatiotemporal tuning (Chapter 3), dependency on a continuous motion trajectory (Chapter 4) and contrast dependent properties (Chapter 5). Surprisingly, our findings revealed an unusual pattern of tuning properties that presented a significant challenge for existing explanations, including those based on predictive interference and spatial summation. We subsequently developed a multi-scale image-based model of motion coding to provide insight into the mechanisms underlying these effects (Chapter 6). By implementing only a few well-established processes we were able to capture a wide range of these tuning properties. The main reason the model can account for these tuning characteristics is the availability of filters tuned to multiple spatial scales in the detection process. We found when the target grating was presented in isolation; simulated contrast sensitivity was determined by the response of filters with tuning preferences that were matched to the stimulus. However, this was rarely the case when targets were presented along with an inducing grating. The model shows the pattern of tuning associated with phase-dependent modulations of sensitivity arises through the recruitment of filters that are not well matched to the target, but that are co-activated by both target and inducing stimuli Aside from phase-dependent modulation of contrast sensitivity in drifting gratings, we also examined the influence of surround phase on the detection of static stimuli. In particular we established the influence of target size, surround configuration and surround contrast (Chapter 7). We found manipulating of the stimulus parameters changed the selectivity of surround suppression from phase-dependent and low-pass tuned to spatial frequency to phase-independent and band-pass tuned. Both experimental data and modeling support the existence of two forms of suppression in static stimuli; a broadly tuned cross-channel component and a narrowly tuned within-channel component. Throughout this thesis we show that contextual interactions can produce some unusual and complex patterns of tuning. Most models designed to account for contextual interactions assume that the mechanism detecting the stimulus is tuned to the properties of the target and localised to the target region. This simplification often makes it difficult to account for these complex patterns of tuning in a single model. Here we have shown that by adopting a multi-scale modeling approach it is possible to account for some of the more perplexing properties associated with the influence of spatial context on visual sensitivity.